Predictors of Self-Compassion in Early Adulthood: The Role of Depression, Stress, Anxiety, and Self-Esteem - Katrim Alifa Putrikita; Malida Fatimah (MOTIVA: JURNAL PSIKOLOGI, 2026)
Self-compassion, or compassion for oneself, is important for young adults because it protects them from the pressures and demands of life. Self-love enables individuals to respond more realistically to life’s demands, allowing them to continue striving without judging or blaming themselves. Empirical findings indicate that self-compassion among early adults tends to range from moderate to low. The process of developing self-compassion in early adults is not easy because various psychological problems commonly influence their level of self-compassion. Psychological problems commonly experienced by early adults are related to depression, stress, anxiety, and self-esteem. This study aims to explore how depression, stress, anxiety, and self-esteem predict and influence the level of self-compassion in early adults. With a deeper understanding of the influence of these factors, it is hoped that more effective ways to increase self-compassion in early adults can be found, which in turn can contribute to mental and emotional well-being. The scales used in this study were the Self-Compassion Scale, DASS 42, and Single-Item Self-Esteem Scale. Data analysis was performed using multiple regression tests. The results of this study indicate that stress was identified as a significant predictor of self-compassion in young adults, while depression, anxiety, and self-esteem do not show a significant influence. These findings indicate that high levels of stress are associated with a decrease in an individual's ability to be kind to themselves when facing difficulties. Based on these findings, it is recommended that practitioners, such as psychologists and counselors, prioritize stress management as an initial intervention to enhance self-compassion in early adulthood.